Decreasing detection frequency of MITE (MCLas-A) in the population of ‘Candidatus Liberibacter asiaticus’ recently collected in southern China - Xue-jin CUI; Chun-hua ZENG; Ke-hong LIU; Cai-ling TENG; Chang-yong ZHOU; Xue-feng WANG (Journal of Integrative Agriculture, 2020)
An active miniature inverted-repeat transposable element (MITE), MCLas-A, was previously identified from ‘Candidatus Liberibacter asiaticus’ known to be associated with citrus Huanglongbing (HLB, yellow shoot disease). To explore the recent transposition status of MCLas-A, 389 ‘Ca. L. asiaticus’ strains collected from nine regions in China were amplified using a specific primer set and three representative ‘Ca. L. asiaticus’ strains were analyzed by next-generation sequencing (NGS) approach. PCR and genomic analysis showed that the entire MCLas-A was only present in 1.80% (7/389) and the jumping-out type of the MITE was predominant (81.23%) in samples tested, suggesting high frequency transposition occurred in ‘Ca. L. asiaticus’ strains recently collected from China. Biological roles of transposition of the active MITE remain to be determined.